Undrained shear strength of soft clay reinforced with 8mm and 16mm diameter a group of bottom ash column - Nurhamizah, Zainal Abidin (2014)
A variety of structures had been constructed almost anywhere, including site which have lower strength of soil layer. Recently stone column has gained acceptance in the geotechnical field since the structure is simple and easy, economical in material used and not bringing significant effect to environment. Bottom ash, as a residue of coal's combustion from coal power plants, has similar properties with sand and there is a potential to use as stone columns. The utilization of the industrial by-products is recognized nowadays due to the continuous dwindling of non-renewable natural materials. Furthermore, the large production of bottom ash from coal burning in Malaysia has results in waste issues. So, by using bottom ash columns, the disposal problem for bottom ash could extensively be reduced. It is necessary to reuse and recycle this material because environmentally friendly and avoid to use of natural and non-renewable resource such as gravel and sand as a replacement in the column using laboratory scale model. The aim of this Final Year Project is to show the improvement level in shear strength of soft clay after being reinforced with group bottom ash columns. The first phase of this study is to determine the physical properties of the material used which is kaolin as soft clay and bottom ash as reinforcing column. In the second phase of study, consolidated kaolin with was reinforced by group of bottom ash column and tested for the shear strength using Unconfined Compression Test. The dimension of the soft clay sample is 50 mm in diameter and 100 mm in height. In this study, five samples of soft clay were fixed. For each sample was installed with group bottom ash column with various in height and size. For the column, the diameter used are 8 mm with height 32 mm, 48 mm, and 64 mm, and for 16 mm diameter, the height of column are and 64 mm, 96 mm, and 100 mm. The highest increment in shear strength was 59.23 % from control sample for 8 mm diameter column. Meanwhile for 16 mm diameter column the increment was about 13.29 % compare to control sample.The installation of bottom ash column as reinforcements had increased the shear strength of the soft clay and the degree of improvement was influenced by the column penetration ration as well as the area replacement ratio.